Secondary School Students Self-Regulated Learning Skill as Predictor of Mathematics Achievement in Imo State Nigeria: Focus on Gender - Duru, Darlington C.; Mba, David O.; Ike, Iheanacho C. (S&Co Publishing, 2023)
Mathematics as an abstract subject, requires the application of cognitive strategies such as self-regulated learning skill to predict students’ achievement. This paper was designed to investigate the secondary school students self-regulated learning skill as a predictor of mathematics achievement with respect to gender. A correlational survey research design was employed. The sample size consisted of 882 senior secondary students class two (SSII) randomly selected from 14 out of 124 public senior secondary schools in Owerri Education Zone of Imo State. Two different instruments were used for data collection. They are Questionnaire on Self-Regulated Learning (QSRL) and Mathematics Achievement Proforma (MAP). Three experts validated the instrument. The Cronbach Alpha calculated yielded a reliability coefficient of 0.89 for QSRL. The data collected were analyzed using Pearson Product-moment correlation coefficient and regression analysis with the aid of Statistical Package for Social Sciences (SPSS) version 20. The findings revealed that self-regulated learning skills significantly predict male students’ achievement in mathematics. The findings also showed that self-regulated learning skill does not significantly predict female students’ achievement in mathematics. It was recommended among others that secondary school students should regulate their learning to increase their mathematics achievement.